EFFECT OF AGING ON THE MICROSTRUCTURES AND MECHANICAL PROPERTIES OF C102 COPPER ALLOY - RIDHWAN, JUMAIDIN; Rafidah , Hasan; Zulfattah, Z. (MTUN UTeM, 2013)
Aging of copper alloy was studied at different temperature and times. Tensile test and metallurgical investigation were carried out to study the effect on mechanical properties and the microstructures of copper alloy. It was observed that peak strength was obtained by specimen aged for 4 hours at 450 oC, with yield strength of 542.38 MPa and ultimate tensile strength of 559.69 MPa. Peak strength was achieved with an increased strain field in the structure produced by coherent precipitates. The finer grain structure was observed in this stage which led to strain hardening. Lowest strength was recorded on specimen aged for 8 hours at 450 oC, with yield strength of 441.66 MPa and ultimate tensile strength of 452.24 MPa. The reduction of strength was the effect of overaging, which was due to coarsening of grain structure and elimination of precipitation coherency.